P505 Early therapeutic drug monitoring after induction therapy with infliximab: correlation with intestinal ultrasound. (27th May 2021) - Nascimento, C; Morão, B; Frias Gomes, C; Cúrdia Gonçalves, T; Castro, F; Moreira, M; Cotter, J; Pereira, F; Caldeira, A; Sousa, R; Coelho, R; Macedo, G; et al.
Abstract: Background: Therapeutic drug monitoring (TDM) in patients receiving infliximab (IFX) has a role in assessing treatment and managing outcomes. Infliximab trough levels (ITL) have been suggested as useful markers for treatment optimization in Crohn's disease (CD).Our goals were: to assess the relationship between ITL and transmural inflammation as assessed by intestinal ultrasound(IUS), following induction therapy with IFX; to assess which clinical, laboratorial or IUS parameters better predicted adequate levels by the end of induction therapy. Methods: Prospective multicentric cohort study including patients with active CD starting IFX therapy. Clinical disease activity assessed using the Harvey-Bradshaw index (HBI), C-reactive protein (CRP), fecal calprotectin (FC) were measured at week 0 and after induction therapy (week 14). IUS was performed at week 0 and 14, bowel wall thickness (BWT) from the worst segment was selected for analysis. Ileocolonoscopy was performed at W0 and SES-CD was registered. ITL were measured at W14. Results: We included 36 patients with CD (61% male; median age 30 years (range 16–73)). According to Montreal classification, most patients were A2 (69%), had ileocolonic disease (L3 56%) and an inflammatory phenotype (B1 58%).Perianal disease was present in 42%. Combination therapy was used in 61%. After induction therapy, 81% were in clinical remission (HBI <5) and 43% had laboratorial remission (normal CRP and FC). IUS response (decrease >25% in BWT) was observed in 24% of patients and remission (BWT normalization) in 11%. Median ITL were 4.3 (IQR 2.3–8.1) and 64% had ITL >3 ug/ml. There was a good negative correlation between ITL and SES-CD (r=-0.492, p=0.003). Adequate ITL were associated with lower HBI (1.5 vs 4.5, p=0.052), laboratory remission (61% vs 15%, p=0.014), lower BWT (4 vs 5.5 mm, p=0.009) and sonographic response (39% vs 0%, p=0.014) at W14. At the end of induction, we found a fair to good correlation between ITL and HBI (r=-0.430, p=0.009), CRP (r=-0, 510, p=0.001), FC (r=-0.590, p=0.001) and BWT (R=-0.506, p=0.002). Receiver operating characteristic (ROC) curve analysis showed that FC at W14 had the largest area under the curve (AUC) in predicting adequate ITL (0.813 vs 0.716 vs 0.739 vs 0.772, p<0.05). Conclusion: Patients with higher disease burden measured by ileocolonoscopy at baseline had lower ITL after induction. Adequate ITL were associated with laboratorial remission and sonographic response at the end of induction, with a good correlation with clinical, laboratorial and sonographic parameters. These findings suggest that adequate IFX levels after induction are associated with a better control of inflammation in IBD, so early proactive TDM during induction may be helpful in treatment management.